Of House and Home: The meanings of housing for women engaged in criminalised street-based sex work - Shdaimah, Corey; Franke, Nancy; Becker, Todd; Leon, Chrysanthi (Anti-Trafficking Review, 2023)
Despite emerging as a core concern for street-based sex workers participating in prostitution diversion programmes (PDPs), housing has received limited empirical attention. In this article, we explore the meanings of housing in the context of court-affiliated PDPs in the US cities of Baltimore and Philadelphia based on interviews and focus groups with 31 PDP participants and 32 criminal legal system professionals. Three themes emerged: (a) housing precarity and crisis mode, (b) housing as a foundation, and (c) housing as an idea(l). PDPs prioritise therapeutic interventions targeting individual behaviours and attitudes over meeting basic needs, often placing programme participants in substandard housing and removing them from existing networks of support. Such prioritisation, which often conflicts with participants’ expressed preferences, does not always leave them better off in the short or long term. PDPs’ neglect of the quality, type, and meaning of housing reveals and reinforces a fundamental disregard for people in street-based sex trade as multifaceted, agentic human beings. We conclude that programmes must prioritise home as a ‘comfort zone’ that must be afforded to all people.